URBANIZATION AND ENVIRONMENTAL DISRUPTION OF CATCHMENT BASINS AS A RESULT OF HOUSING DEVELOPMENT AT CIDADE OPERARIA AND ADJACENCIES, MARANHAO ISLAND - Izis Deise Silva de Sousa; Geiza Paula de Sousa Veloso; Luiz Jorge Bezerra da Silva Dias (Revista Sociedade & Natureza, 2005)
The Industrial Revolution was followed by an increase in the rates of urbanization, particularlyafter the second-half of the 20th century. In this context, Sao Luis, the capital city ofMaranhao State, adopted a housing development policy that was aimed at reducing thehousing deficit in the municipality. The construction of the Cidade Operaria housing complexwas a response to these explicit social needs, which have intensified since the 1970s. Theoccupation of the complex, however, resulted in considerable damage to the ecologicalintegrity of the adjacent habitats. The complex is located in the catchment basin of thePaciencia and Santo Antonio rivers, at the center of the Maranhao Island. This study analyzesthe spatial and temporal dynamics of the area’s urbanization process, which occurred in threephases: the period between 1976 and 1981 saw the removal of the original vegetation cover insome areas, as a result of the first settlement in Parque Zelandia. During that period,subsistence agriculture was common practice along the margins of streams and rivers. Thesecond phase corresponds to the construction of the Cidade Operaria housing complex, whichoccurred between 1981 and 1988. During that time, 860 ha of land were cleared andurbanized, resulting in considerable environmental damage. Changes of relief, due to gradingand earthmoving activities, lead to irreversible modifications in the course of rivers andstreams; many tributaries of the rivers Paciencia and Santo Antonio had theirs springssmothered by earthfills; construction of houses and the use of asphalt on roads reduced soilpermeability, increasing the depth of the water table; the release of untreated sewagecontaminated the drainage basins. During the third phase, which started in 1988, theenvironmental degradation was intensified by the occupation of areas adjacent to the housingcomplex. This model of urbanization has caused irreversible damage to the hydrology andwater quality in the study area, and this article aims to provide an incentive for the creation ofland-use planning and management strategies that include protective and restorative measuresto reduce degradation of catchment basins as a result of urbanization.